Development of multi-input sensor algorithm for autonomous underwater vehicle (AUV) system stage 2 - Mohd Aras, Mohd Shahrieel; Harun, Mohd Haniff; Mohamad, Mahirah (2010)
This project is to develop a multi-input algorithm of sensors for Autonomous Underwater Vehicle (AUV) system for the stage two which is having high performance automated detection and monitoring on underwater application or for surveillances and defense application. The sensors implemented in AUV such as vision system, hydrophone system and sonar system successful develop in stage one. While in stage two we improved some multi-input sensor such as GPS system and compass module with pressure and temperature sensor system. In the stage one all multi-input sensor gives the best performances. The new design of vision system for AUV with the implementation of wireless camera, whereby, produce clearer image. The ultrasonic sensor is a main device to transmit and receive the signal from the obstacle.The ultrasonic sensor will be combined to the ultrasonic circuit. Hydrophone is an underwater microphone which with the help of pressure impulses of acoustic waves converts them into electrical signals which in further are used for communication. It was designed to be used underwater for recording or listening to underwater sound. In stage two GPS system uses to navigation the AUV which is using Smart GPS Receiver model EB-85A and GPS Engine Board EB-230. This design could easily be expended and made portable for use in AUV. In this project also aims to obtain data on pressure and temperature in the water around AUV and shows the relationship between pressure and water depth and pressure with temperature. The entire sensor produced the good result and all result analyzed stated in this paper.